“The Immense Odds Against the Fossil’s Occurrence”:: The Poetry of Christopher Dewdney as Materialist Historiography - Hlibchuk, Geoffrey (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
Of central importance to the poetry of Christopher Dewdney is the historicity of nature, and, chiasmatically, the nature of history. This importance is often overlooked by critics, who tend to bypass the historical dimension of Dewdney's writing in favour of an atemporal solipsism. Such an approach, which sees his poetry as documenting "the solipsism of consciousness" (Hepburn 32), lessens the historical impact of the work and instead emphasizes a "Dream of Self " as the centripetal force of Dewdney's writing. The complex interplay of nature and history in Dewdney's poetry is frequently subordinated in favour of more ahistorical or postmodern theoretical Lacanian psychoanalysis, and neurobiology. These approaches have led critics to see his poetry as a site wherein temporality is "thought to occur simultaneously," effectively neutralizing the complex historical juxtapositions that his texts create.